Motivasi Mahasiswa Kebidanan Semester V Dengan Penghargaan Diri Praktik Klinik Kebidanan II (PKK II) (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: The success of the study can be supported by several factors, both from within and from outside. The success of the study can be supported by several factors, both factors which come from within and from outside. Academy midwifery yogyakarta a favorite course of study because of accreditation BAN-PT with accreditation “A”, and interest registrants in 2012 to reach 1,000 more applicants, and received about 250 after passing the selection board test, medical, and psychological test. Midwifery academic competition in providing educational programs as well as possible, with the demands of the workforce skill abilities of students and graduates in print professional and independent midwife, based on the data according to the records of PP IBI, now there are 200’s of thousands of graduates of obstetrics and already 101 thousand registered as a member of the PP IBI. Each year there are 29 thousand new midwife. “With this comparison, it is estimated by 2015 there will be a surplus of midwives,3). it is of course necessary to get the attention of students who are still actively improving skills, according to the field of obstetrics.Purpose: To determine the relationship between student motivation fifth semester with Self Award Midwifery Clinical Practice (PKK II)Methods: This descriptive analytic study, cross-sectional approach, with Kendall Tau analysis, data were collected by questionnaire, sampling using proportional random sampling technique in mothers and infants number 67 respondents.Results: The relationship between student motivation fifth semester with Self Award Midwifery Clinical Practice (PKK II). hypothesis testing using SPSS analysis Kendall’s Tau obtained value (Kendall’s Tau) with a probability value (Asyimp.Sig) of 0.021. Significance level of 5%.Conclusion: the relationship between student motivation fifth semester with Self Award Midwifery Clinical Practice (PKK II).Keywords: Motivation, V Semester Student, Self-esteem, Midwifery Clinical Practice II.